Immediate Implant Placement at an Inflammatory Periapical Cyst Site in the Aesthetic Area - Alexandre Perez; Mathilde Layac; Tommaso Lombardi (MDPI AG, 2024)
A healthy 47-year-old woman consulted the Oral Surgery and Implantology Unit of the University Hospitals of Geneva with a request to treat her painful tooth 11 and replace the missing tooth 21. The dental history revealed that the patient had lost teeth 21 and 22 due to advanced caries. On clinical examination, tooth 11 showed an ill-fitting prosthetic crown with overhanging margins, an increased localized probing depth of 8 mm in the disto-vestibular area, and sensitivity to percussion. The edentulous site 21 showed horizontal bone atrophy. Radiological examination revealed a well-defined unilocular radiotransparent lesion surrounded by a thin radiolucent border, located at the apex of tooth 11 and measuring 10 × 8 mm. The treatment consisted of extraction of 11, enucleation of the apical lesion, and insertion of implants at sites 11 and 21 with simultaneous bone augmentation in a single surgical procedure, with aesthetic and functional results at 3-year follow-up without any complications. Our case highlights that immediate implant placement in cases of cystic periapical lesions represents a good valid alternative to standard treatment.